Bioequivalence study of the two 1.5 g cefoperazone and sulbactam IM injections in Thai healthy male volunteers - Kaewvichit S. (2014)
Objective: To perform a bioequivalence study of the two 1.5 g cefoperazone (1.0 g) and sulbactam (0.5 g) between Cefper® and Sulperazon® injections. Material and Method: The present study was performed in 24 Thai healthy male volunteers who were intramuscularly injected a single dose of 1.5 g cefoperazone and sulbactam. A single dose, two periods, two sequences, double blind randomized crossover with a one-week washout period was used. Blood samples were collected before and at 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 4, 6, 8, and 12 hours after intramuscular injection and determined for cefoperazone and sulbactam plasma concentration by validated HPLC- UV methods. The pharmacokinetic parameters were analyzed by noncompartmental analysis and the ANOVA was carried out. Results: Tmax of both cefoperazone and sulbactam for volunteers who were injected with either Cefper® or Sulperazon® injection were not significantly different (p > 0.05). The 90% confidence intervals of the log of ratio of either Cmax or AUClast or AUCinf of both cefoperazone and sulbactam between 1.5 g Cefper® and Sulperazon® injections were within the bioequivalence range of 0.80-1.25. Conclusion: The 1.5 g cefoperazone and sulbactam injection of Cefper® and Sulperazon® used in the present study are bioequivalent.